Evaluasi Tepung dan Infusum Kacang Hijau (Vigna radiata) sebagai Media Alternatif Pertumbuhan Staphylococcus aureus - Febri Sembiring; Suparni; Dewi Setiyawati; Wardati Humaira; Sri Widia Ningsih; Nin Suharti; Astrid Siska Pratiwi (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
Limited access to and the high cost of commercial growth media have driven the development of alternative media based on locally available materials. Although several legume-based materials have been reported to support bacterial growth, the use of mung beans (Vigna radiata) as an alternative medium—particularly in the form of flour and infusion—and comparisons of their effectiveness against standard media remain limited. This study aims to evaluate the potential of these two forms as growth media for Staphylococcus aureus. This was an experimental study conducted from March to May 2024 at the Microbiology Laboratory of the Medan Public Health Polytechnic (Poltekkes Kemenkes). The method used was growth analysis via the Total Plate Count (TPC) method. The results showed that the average TPC of S. aureus on mung bean flour medium was 1.07 × 10⁷ CFU/mL, and on mung bean infusion medium it was 4.7 × 10⁶ CFU/mL, whereas TSA medium, as the standard medium, yielded 5.8Z× 10⁶ CFU/mL. This indicates that both forms of the mung bean alternative media were capable of supporting optimal bacterial growth, with the flour medium yielding a higher cell count compared to the standard medium (TSA). Morphologically, the colonies on the alternative media were smaller (±2 mm, yellowish-white) compared to those on TSA (±3 mm, yellow). Thus, it can be concluded that mung bean flour has the potential to be an effective alternative medium for growing S. aureus compared to the infusion medium, which is less optimal due to the possible degradation of nutrients during the heating process.